Basic Physical Education of Children in Islam (Abdullah Nashih Ulwan's Perspective Analysis in the Book of Tarbiyatul Aulad Fil Islam) - Norhabibah Norhabibah Norhabibah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Currently, there are more and more phenomena of attitudes or habits that can damage the body or body which has a negative impact on the faith, morals, psychology and minds of children. So that in this case it is important for parents and educators to know and understand the big responsibility in providing basic physical education to their children according to Islamic teachings. The purpose of this research is to find out the basic physical education of children in Islam according to Abdullah Nashih Ulwan. This research is a type of library research, namely research conducted through critical and in-depth assessment of library materials that are considered relevant to the research topic. The results of this study show that basic physical education for children in Islam includes: 1) Providing a good, lawful living for their family and children, 2) Following health rules in eating, drinking and sleeping; 3) Protect yourself from infectious diseases; 4) Treat Diseases; 5) Principles of not endangering oneself and others; 6) Familiarize children with sports and riding, such as the sport recommended by the Prophet. namely; archery, swimming, horse riding, and spear throwing practice; 7) Familiarize children to be zuhud and not dissolve in pleasures; 8) Instill firm character, attack children and stay away from reactions, deviations and mischiefs.Keywords: Children, Islam, Physical Education